Sistem Monitoring Daya Listrik Berbasis Internet of Things Menggunakan Aplikasi Blynk - Rifa; Risky Sandiari; Joni Eka Candra; Zainul Munir (LPPM-ITEBA, 2024)
This research aims to design and implement a monitoring system that allows the measurement of voltage, current, and power using electronic devices, particularly NodeMCU and PZEM004T current sensor, along with the Blynk application as the user interface. The development method used is the waterfall method, involving stages of analysis, design, implementation, testing, and evaluation.This monitoring system is designed to measure voltage, current, and power for various electronic devices at home or in the surrounding environment. However, the measurement results obtained show errors, especially in current measurement. The current measurement results have a significant error rate, which can affect the accuracy of power calculations. The error testing results for the voltage sensor are 3W lamp (0.171%), 10W lamp (0.343%), and the overall average voltage sensor error is 0.410%, the average errors for the current sensor are (92%), power (1.57%), and the total cost of electricity that will be paid for a month is (Rp.89,232)..